1999
DOI: 10.1029/1999jb900047
|View full text |Cite
|
Sign up to set email alerts
|

A detailed record of paleomagnetic field change from Searles Lake, California: 1. Long‐term secular variation bounding the Gauss/Matuyama polarity reversal

Abstract: Clement, 1992] intimates that the field may commonly show signs of early instability. This precursory event is actually one of a sequence of oscillations (in inclination and intensity) preceding the transition. That these fluctuations occur at roughly 4 kyr intervals leading up to the reversal (which also appears at this same interval) strongly suggests that an oscillatory disturbance in the core, active over at least 15 kyr prior to the transition, had eventually triggered the reversal. In addition, that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In other words, no dipole field could exist during the fairly long time of the pole switching. This view offered by S. I. Braginskii agrees with the conclusions advanced by Gurarii [1988], Clement [2004], and other authors, and is of great interest in terms of the physical nature of the dipole and nondipole field.…”
Section: Magnetic Moment Decline and Restoration The Duration Of Invsupporting
confidence: 87%
See 2 more Smart Citations
“…In other words, no dipole field could exist during the fairly long time of the pole switching. This view offered by S. I. Braginskii agrees with the conclusions advanced by Gurarii [1988], Clement [2004], and other authors, and is of great interest in terms of the physical nature of the dipole and nondipole field.…”
Section: Magnetic Moment Decline and Restoration The Duration Of Invsupporting
confidence: 87%
“…[10] The analysis of the paleointensity data variation during and in the vicinity of the reversals showed that the average decline of the magnetic field during its reversals had been as high as seven times [Gurarii, 1988]. This estimate was obtained for the reversals of the last 15 million years, using the data published prior to 1986.…”
Section: Magnetic Moment Decline and Restoration The Duration Of Invmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 shows another complex, high-resolution record of a different reversal, the Gauss/Matuyama transition recorded in a core of lacustrine sediment from eastern California [Glen et al, 1999b]. Based on detailed magnetostratigraphy, the average deposition rate was about 22 cm/kyr during late-Gauss and early Matuyama time, almost twice that of the previous example, and the lithololgy is uniform [Liddicoat, 1982;Glen et al, 1999a]. The core was sampled continuously at 1-cm spacing through a 2.1 m stratigraphic interval centered on the transition, with two or three 1-cm cubic specimens measured at each level.…”
Section: Some Illustrative Polarity Transition Recordsmentioning
confidence: 99%
“…Optimum demagnetization is tuned to eliminating viscous overprints without rendering the signal unmeasurably weak. In recent studies, a wide variety of fields and temperatures were used: 10 mT [ Peck et al , 1996; Yamazaki et al , 1995], 15 mT [ Verosub et al , 1996; Yamazaki and Ioka , 1994], 17.5 mT [ Tauxe and Hartl , 1997], 20 mT [ Clement and Kent , 1991; Meynadier et al , 1994, 1995; Tric et al , 1992; Valet et al , 1994; Yamazaki and Oda , 2001, 2002], 25 mT [ Roberts et al , 1997], 30 mT [ Haag , 2000; Pan et al , 2001], 40 mT, [ Glen et al , 1999], averages of more than two steps [ Brachfeld and Banerjee , 2000; Channell et al , 2002; Dinares‐Turell et al , 2002; Guyodo et al , 2001; Meynadier et al , 1992], and thermal demagnetization to 420°C [ Laj et al , 1996]. …”
Section: Implications For Paleomagnetism and Paleointensity Determinamentioning
confidence: 99%